Antitumor and Immunomodulatory Effects of Polysaccharides from Broken-Spore of Ganoderma lucidum - Wang, Peng-Yun; Zhu, Xiao-Ling; Lin, Zhi-Bin (Frontiers in Pharmacology, 2012)
The antitumor activity of Gl-BSP, a polysaccharide isolated from boiling water extract of the broken-spores of Ganoderma lucidum (Leyss ex Fr) Karst. and its possible mechanism were investigated in vivo and in vitro. It was showed that Gl-BSP (50, 100, 200 mg/kg) exhibited antitumor effect against Sarcoma 180 (S180) in BALB/c mice. The Gl-BSP was not cytotoxicity in S180 cells and PG cells (human lung carcinoma cell) in vitro. However, Gl-BSP-treated serum potently inhibited S180 cells and PG cells proliferation in vitro. Moreover, Gl-BSP could promote the splenic lymphocyte proliferation induced by Con A or LPS, enhance nature killer cell (NK cell) cytotoxic activity, augment the percentage of neutral red (NR) phagocytosis by macrophages, and increase the percentage of the CD4+ or CD8+ subset in S180-bearing BALB/c mice. The level of IFN-γ, TNF-α and NO of serum apparently was increased by Gl-BSP. Gl-BSP also showed immunomodulatory activities in tumor-bearing mice. Furthermore，It was proved that neutralization with anti-TNF-α and/or anti-IFN-γ significantly diminished growth inhibition induced by Gl-BSP –treated serum in S180 or PG cells. Blocking effect was noted in the combination of anti-TNF-α and anti-IFN-γ. These observations suggest that the antitumor activity of Gl-BSP may mainly relate to the activation of the immune response of the host organism by the stimulation of NK cells, T cells, and macrophages.